Input Trade and the Location of Production - Findlay, Ronald; Jones, Ronald W (American Economic Review, 2001)
Stanley Engerman has been a presence in the Department of Economics at the University of Rochester for over 37 years. He was an early and eminent participant in the Cliometric Revolution that swept throughout the economichistory profession in the 1960’s and 1970’s. We doubt that anyone could have anticipated the “gathering storm” that greeted the publication of Time on the Cross, co-authored with Robert Fogel in 1974. Since that time Stan has become the world’s leading authority on slavery in the Americas and the Caribbean, as well as an important contributor to a set of issues ranging from the 19th century American iron industry to the economics of British imperialism. His own human capital, as extensive as we know it to be, is complemented by capital of the physical variety: an enormous library of research material spilling over into bookshelves and floors in several offices in Rochester and attracting a yearly stream of itinerant scholars anxious to pick his books as well as his brains. In this short note, we intend to honor Stan by applying the tools of international trade theory to illustrate several episodes in the development of industries, both in the United States and in world markets. A colleague of Stan’s at Rochester, Lionel McKenzie, once commented that, in 19th century Britain, Lancashire would have been unlikely to produce cotton cloth if the cotton had to be grown in England (McKenzie, 1954). This remark expresses in utter brevity the importance to production and trading patterns of the domain of tradability of raw materials or intermediate products. For example, it is difficult to envisage the patterns of production (and trade) in modern-day Japan should it be denied access to world supplies of oil, coal, and iron ore, local production of each of these items being negligible. Transport costs as well as man-made impediments to trade are mainly responsible for variations in the degree of access countries possess to the inputs available in the markets of other countries. Simple competitive generalequilibrium models of production, of the type intensively utilized in the theory of international trade, can usefully be harnessed to shed light on several episodes in 19th century American economic history in which the nature of trading possibilities for raw materials heavily influenced the extent to which local American production of final commodities could withstand the pressures in world markets without the aid of protective devices. The simplest model setting in which to investigate the importance of trade in raw materials is a Ricardian model, augmented by the necessity of using a produced input in addition to labor in at least one commodity. Denote the pair of final commodities by X and Y, where in order to produce Y a certain quantity of intermediate good, Z, is required. The competitive profit conditions for the two final commodities are shown in equation (1):